Analisis Strategi Pemasaran Dalam Meningkatkan Jumlah Kepesertaan Pada BPJS Ketenagakerjaan Kantor Cabang Bandar Lampung - Zsazsa Mayori; Vonny Tiara Narundana (Jurnal Manajemen dan Bisnis (JMB), 2021)
AbstractIt seems that the awareness of Non-Receiving Wages (BPU) workers following the BPJS Ketenagakerjaan membership appears to be lacking. This can be seen from the decline in BPU participation in the BPJS Ketenagakerjaan Bandar Lampung Branch. BPU are those who work in the informal sector, such as traders, pedicab drivers, public transportation drivers, domestic helpers, parking attendants, farmers, and fishermen. In 2018, the number of BPU memberships in BPJS Ketenagakerjaan Bandar Lampung reached more than 16,000 workers. In 2019, there were only 14,818 workers. The reason is that they (BPU workers) admit that they cannot experience the benefits directly. In fact, by joining the BPJS Ketenagakerjaan membership, you will get many benefits. The selected program can also be gradual, according to the abilities and needs of the participants. It can also be seen that Construction Service Participants in the table above have decreased, if in 2018 there were more than 259,000 workers, while in 2019 it decreased to 246,746 workers. The purpose of this study is to find out and explain how the marketing strategy is to increase the number of BPJS Ketenagakerjaan memberships at the Bandar Lampung branch office. The method used in this study is a qualitative analysis method, using a SWOT analysis tool (strength, weakness, opportunity, and threat). The SO strategy implemented is to cooperate with the government so that it can create many opportunities to improve the quality of the social security program, there is cooperation that can be carried out by BPJS Ketenagakerjaan with government agencies to run a pension security program, and maintain a pension security program for workers and help in treatment so as to improve the welfare of workers and make the company lessen the medical burden on workers. Keywords: Analysis SWOT, Marketing Strategy, Participation